2015
DOI: 10.1007/s13202-015-0218-2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fluid characterization on compositional gradient in a volatile oil reservoir

Abstract: Compositional gradient known as a potential of vertically variations in composition (and sometimes areal changes) has a remarkable effect on reservoir management steps such as estimation of initial hydrocarbon in place, design of downstream equipments and prediction of gas-oil contact. One of the main steps in development of compositional grading is to characterize fluid sample. In this study, compositional grading is studied in a volatile oil sample from an oil field in south of Iran. Implemented models are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Contrary to the general view that compositional grading depends on fluid samples and their characterization, Kiani et al [9] reported that the augmentation of fluid characterization by splitting plus fractions of fluid composition did not have a significant impact on the compositional gradings of both hydrocarbons and non-hydrocarbons in a given system. However, it is understood that GOC prediction from CGS is sensitive to the quality and representativeness of the underlying PVT dataset.…”
Section: List Of Symbols Amentioning
confidence: 88%
“…Contrary to the general view that compositional grading depends on fluid samples and their characterization, Kiani et al [9] reported that the augmentation of fluid characterization by splitting plus fractions of fluid composition did not have a significant impact on the compositional gradings of both hydrocarbons and non-hydrocarbons in a given system. However, it is understood that GOC prediction from CGS is sensitive to the quality and representativeness of the underlying PVT dataset.…”
Section: List Of Symbols Amentioning
confidence: 88%
“…Many other scientists have studied many other factors that lead to the composition of petroleum fluids in subsurface circumstances including: thermal diffusion by Dougherty and Drickamer in 1955 [6], asphaltene precipitation by Riemens et al in 1988 [48], capillary forces by Lee in 1989 in [27] and Wheaton in 1991 [54], biodegradation by Temeng et al in 1998 [53], genesis by Smalley and England in 1992 [51], natural convection by Ghorayeb and Firoozabadi in [12], unsteady flux of a water aquifer partly contacting a reservoir by Hoier and Whitson in 2001 [16], reservoir compartmentalization by Elshahawi et al in 2005 [7], and incomplete hydrocarbon migration by Gibson et al in 2006 [14]. Enormous research in this area is still active (see [5,18,26,30,38,39,41,42,52] and references therein).…”
Section: Introductionmentioning
confidence: 99%